Initial drainage‐related prognostic factors for perihilar cholangiocarcinoma: A single‐center retrospective study. Issue 1 (22nd May 2022) - Sato, Katsuhiko; Shigekawa, Minoru; Kozumi, Kazuhiro; Okabe, Junya; Sato, Yu; Tamura, Takeshi; Yoshioka, Teppei; Sakamori, Ryotaro; Iwagami, Yoshifumi; Yamada, Daisaku; Tomimaru, Yoshito; Noda, Takehiro; et al.
Abstract: Objectives: Perihilar cholangiocarcinoma (PCC) is a complex disorder involving the hepatic hilum. Multiple endoscopic retrograde cholangiopancreatography sessions are necessary for diagnosis and treatment with underlying cholangitis risk. Our aim is to clarify the initial‐drainage‐related prognostic factors of PCC. Methods: This study was a single‐center retrospective study. A total of 104 consecutive patients diagnosed with PCC from January 2010 to February 2020 were enrolled. We defined the diagnostic period as the time between the first biliary drainage attempt and the final drainage when treatment, including surgery or chemotherapy, was started. We focused on this initial period and analyzed the endoscopy‐related factors that affected mortality. Results: Overall survival of all PCC patients was 599 days. Overall survival of surgically treated patients and unresectable patients were 893 days and 512 days, respectively. In 48 surgically treated patients, drainage‐related cholangitis within the diagnostic period, defined as new cholangitis that occurred after the first biliary drainage attempt, worsened overall survival from 1460 days to 607 days. Endoscopic sphincterotomy, the first drainage method other than endoscopic nasobiliary drainage, and four or more endoscopic retrograde cholangiopancreatography sessions were risk factors for drainage‐related cholangitis. Drainage‐related cholangitis increased pathological lymph node metastasis. Percutaneous transhepatic biliary drainage as final drainage was the only prognostic factor in unresectable chemotherapy‐treated patients. Conclusions: Drainage‐related cholangitis worsened the prognosis in PCC patients who underwent surgery. Appropriate endoscopic retrograde cholangiopancreatography strategies, especially during the diagnostic period, are of great importance in PCC.